2017
DOI: 10.1093/neuonc/nox036.459
|View full text |Cite
|
Sign up to set email alerts
|

P17.13 Dosimetric comparison and feasibility of simultaneous integrated boost (SIB) in treatment of malignant gliomas using intensity modulated radiotherapy (IMRT) or volumetric modulated arc therapy (VMAT)

Abstract: Abstracts iii119NEURO-ONCOLOGY • MAY 2017 extracted and XRCC1 gene SNPs were analyzed; the allelic discrimination was performed using an ABI PRISM 7900 SDS (Applied Biosystems, Carlsbad, CA, USA) and with validated TaqMan ® SNP genotyping assays (Applied Biosystems). Kaplan Meier curves were performed for statistical association with genotypes. The study has been approved by the local IRB. RESULTS: At the data analysis, the median progression-free survival (PFS) and median overall survival (OS) of these pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…They also found that MU and treatment time were reduced in the VMAT plan (p < 0.001). 16,17 This particular study did not show any dosimetric advantage of VMAT over IMRT.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…They also found that MU and treatment time were reduced in the VMAT plan (p < 0.001). 16,17 This particular study did not show any dosimetric advantage of VMAT over IMRT.…”
Section: Discussionmentioning
confidence: 58%
“…However, other studies have shown some data that are different from ours and this could be due to the smaller sample size in our study. [15][16][17][18] Pragna et al in 2018 did a dosimetric comparison between IMRT and VMAT plan in 28 patients for glioma. Among the two plans, they found that IMRT had better PTV coverage at the expense of mean dose to the brain.…”
Section: Discussionmentioning
confidence: 99%